Exposures to Air Pollution and Risk of Acute-onset Placental Abruption: A Case-crossover Study. Issue 5 (September 2018) - Ananth, Cande V.; Kioumourtzoglou, Marianthi-Anna; Huang, Yongmei; Ross, Zev; Friedman, Alexander M.; Williams, Michelle A.; Wang, Shuang; Mittleman, Murray A.; Schwartz, Joel
Abstract : Background: Despite abruption's elusive etiology, knowledge of triggers that precede it by just a few days prior to delivery may help to understand the underpinnings of this acute obstetrical complication. We examine whether air pollution exposures immediately preceding delivery are associated with acute-onset abruptions. Methods: We applied a bidirectional, time-stratified, case-crossover design to births with an abruption diagnosis in New York City, 2008–2014. We measured ambient fine particulate matter (PM2.5 ) and nitrogen dioxide (NO2 ). We fit distributed lag nonlinear models based on conditional logistic regression to evaluate individual exposure and cumulative exposures over lags 0–7 days before abruption, adjusted for temperature and relative humidity (similar lags to the main exposures). Results: We identified 1, 190 abruption cases. We observed increased odds of abruption for exposure to PM2.5 (per 10 μg/m 3 ) on lag day 3 (odds ratio [OR] 1.19, 95% confidence interval [CI] = 0.98, 1.43), lag day 4 (OR 1.21, 95% CI = 1.01, 1.46), and lag day 5 (OR 1.17, 95% CI = 1.03, 1.33). Similarly, the odds of abruption increased with exposure to NO2 (per 5 ppb) on lag day 3 (OR 1.16, 95% CI = 0.98, 1.37), lag day 4 (OR 1.19, 95% CI = 1.02, 1.39), and lag day 5 (OR 1.16, 95% CI = 1.05, 1.27). Exposures to PM2.5 and NO2 at other lags, or cumulative exposures, were not associated with abruption of acute onset. Conclusions: This case-crossover study showed evidence of an association between short-term ambient air pollution exposures and increased abruption risk of acute onset. Abstract : Supplemental Digital Content is available in the text.